Early Experiences Engaging Patients Through Patient and Family Advisory Councils. Issue 4 (October 2016) - Peikes, Deborah; O'Malley, Ann S.; Wilson, Claire; Crosson, Jesse; Gaddes, Rachel; Natzke, Brenda; Day, Timothy J.; Cromp, DeAnn; Keith, Rosalind; Little, Jasmine; Ralston, James
Abstract : Primary care practices are increasingly asked to engage patients in improving care delivery. We report early experiences with Patient and Family Advisory Councils (PFACs) from interviews of patients and practice staff in the Comprehensive Primary Care initiative, and identify ways to improve PFACs. Patients and practice staff report PFACs help practices elicit patient feedback and, in response, improve care delivery. Nonetheless, there are areas for refinement, including recruiting more diverse patients, providing an orientation to members, overcoming reticence of some patients to raise issues, and increasing transparency by sharing progress with PFAC members and patients in the practice more generally. Abstract : Supplemental Digital Content is Available in the Text.